2001
DOI: 10.1007/s002660010139
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Compression After Breast Augmentation

Abstract: In a randomized study of 130 patients undergoing breast augmentation, postoperative compression did not reduce the frequency of postoperative bruising or hematoma formation, and 37.5% of the 64 patients having compression had complaints regarding their use. Postoperative compression is of no value after breast augmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…22 There were no differences in bruising or hematomas. BarMeir et al reviewed the information available and concluded that silicone gel-filled implants do not affect the incidence of connective tissue diseases.…”
Section: Evidence On Postoperative Outcomesmentioning
confidence: 87%
“…22 There were no differences in bruising or hematomas. BarMeir et al reviewed the information available and concluded that silicone gel-filled implants do not affect the incidence of connective tissue diseases.…”
Section: Evidence On Postoperative Outcomesmentioning
confidence: 87%
“…The use of compressive garments in breast aesthetic surgery is a constant practice in decreasing post-surgical oedema and haematoma risk, but Nathan and Singh [ 21 ] recently found that compression has a limited effect in the management of post-surgical oedema in breast surgery and very often these garments cause patient discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…Different methods are used to decrease post-operative oedema from the use of drain [ 2 – 4 ], compression garments [ 5 ] and ice bags [ 6 ] to medical therapies based on corticosteroids and non-steroidal anti-inflammatory drugs (NSAIDs) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The breast band is wrapped around the top portion of the breast and superior to the implant to keep implants in the lowest possible position throughout the early healing phase. [4][5][6] Patients are instructed to wear the breast band at all times, except when showering. The purpose for wearing the band at all times is to ensure the implants remain in the most inferior breast pocket, giving the body enough time to form the protective capsule.…”
Section: Introductionmentioning
confidence: 99%